PEMBINAAN MASYARAKAT TENTANG KOMERSIALISASI DAN STERILISASI INDUSTRI PADA PENGOLAHAN ABON SAPI - Yofitri Heny Wahyuli; Asmawati; Aryanisila; Holipah (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community partnership service aims to increase community productivity and income by empowering the people's economy and assisting small and medium businesses with stimulant skills in the field of technology and hygienic management of the production of "Abon Beef" brand in the city of Palembang. The stages of implementing this community service program begin with an integrated approach carried out from the initial process of socialization and planning during which the activity lasts effectively for approximately 3 months. In the initial socialization, the team invited workers involved in the process of making fish floss to socialize the activities carried out so that effective and reciprocal communication occurred. The coaching that will be carried out by the service will continue with the management of the processing of shredded tuna "Beef Shredded" to be better by improving product quality and marketing carried out by the owner and also improving the management system. Shredded products will have their own labels and will then be marketed via e-commerce platforms.